2022
DOI: 10.1001/jamacardio.2022.0219
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients With Catecholaminergic Polymorphic Ventricular Tachycardia Treated With β-Blockers

Abstract: IMPORTANCEPatients with catecholaminergic polymorphic ventricular tachycardia (CPVT) may experience life-threatening arrhythmic events (LTAEs) despite β-blocker treatment. Further complicating management, the role of implantable cardioverter defibrillator (ICD) in CPVT is debated.OBJECTIVE To investigate the long-term outcomes of patients with RYR2 CPVT treated with β-blockers only and the cost to benefit ratio of ICD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 30 publications
2
25
0
4
Order By: Relevance
“…According to European Society of Cardiology guidelines [ 51 ], the first-line therapy for CPVT is beta-blockers to suppress the catecholamine stimulation of the β-adrenergic pathway. It was very recently reported that non-selective β-blockers (nadolol, propranolol) were more efficient at reducing the risk of life-threatening arrhythmic events compared with selective β-blockers [ 52 ]. If beta-blocker therapy is ineffective, additional treatment with flecainide is recommended.…”
Section: Cardiac Disease Associated With Ryr2 Mutationsmentioning
confidence: 99%
“…According to European Society of Cardiology guidelines [ 51 ], the first-line therapy for CPVT is beta-blockers to suppress the catecholamine stimulation of the β-adrenergic pathway. It was very recently reported that non-selective β-blockers (nadolol, propranolol) were more efficient at reducing the risk of life-threatening arrhythmic events compared with selective β-blockers [ 52 ]. If beta-blocker therapy is ineffective, additional treatment with flecainide is recommended.…”
Section: Cardiac Disease Associated With Ryr2 Mutationsmentioning
confidence: 99%
“…In this cohort, the de novo cases presented with an arrhythmic event (syncope or cardiac arrest) at a younger age. 41 Lifestyle changes and supportive care are crucial for all patients with CPVT. Furthermore, all patients with CPVT should be treated with pharmacological therapies to reduce the incidence of the primary manifestations of the disease.…”
Section: Risk Stratification and Treatmentmentioning
confidence: 99%
“…Notably, data on long-term arrhythmic events in CPVT patients on dual therapy (β-blocker and flecainide) with or without LCSD are still lacking. 41 Based on the data available and in the absence of randomised trials, it seems reasonable to recommend a conservative approach towards using ICDs in patients with CPVT in line with the current guidelines. Indeed, when an ICD is implanted following a shared decision-making process, the treating physician should seek to minimise the risk of appropriate and inappropriate therapy by optimising medical treatment with or without LCSD.…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Amongst patients who survived an attempt of SCD, or present with syncope/sustained VT/VF despite maximal medical therapy, current evidence recommends the use of an implantable cardioverter-defibrillator (ICD) for primary/secondary SCD prevention [ 18 , 19 , 20 ]. However, although ICD implantation is associated with reduced mortality amongst high risk CPVT patients, it should be noted that ICD shocks come with a risk of triggering ventricular tachyarrhythmia under a vicious cycle of adrenergic stimulation, thus potentially increasing the morbidity and mortality amongst this cohort of patients [ 21 ].…”
Section: Introductionmentioning
confidence: 99%